The Physiological Role of GABA in Fine-Tuning Control of Blood Glucose and Diabetes Treatment - Mohsen Davari; Shahla Sohrabipour; Atefeh Golkari (Disease and Diagnosis)
Diabetes mellitus is characterized by elevated blood glucose levels, manifesting during fasting or after meals. According to projections by the International Diabetes Federation, the global incidence of diabetes was approximately 366 million individuals in 2011, with an anticipated increase to 552 million by 2030. The pancreatic islets play an essential role in regulating blood glucose concentrations. The intercellular communication between α- and β-cells within the pancreatic islets plays a critical role, which is more intricate and less understood than their systemic hormonal effects on preserving glucose homeostasis and balancing the secretion of glucagon and insulin. Research has identified several substances within insulin vesicles that modulate α- and β-cell populations through paracrine interactions, thereby intricately regulating the secretion of insulin and glucagon. These substances encompass insulin-like growth factors, macrophage migration inhibitory factors, pituitary adenylate cyclase-activating polypeptide, preptin, and gamma-aminobutyric acid (GABA). In normal individuals, insulin in α-cells, through insulin receptors and the mammalian target of rapamycin/protein kinase B/phosphatidylinositol-3-kinase pathway, causes α-cells to proliferate and ultimately increase blood glucagon. Nonetheless, GABA is secreted in addition to insulin. GABA via GABA-A receptors causes α-cells to be hyperpolarized and balance the proliferation of α-cells. This regulates the ratio of the number of α-cells to β-cells, which ultimately fine tune blood glucose. This review indicates that GABA, as a medicinal compound that has no prominent side effects, can have effects on reducing blood glucose and improving other diabetic markers similar to insulin.